Resonant Excitation of Shear Alfvén Perturbations by Trapped Energetic Ions in a Tokamak - Abel, I; Breizman, B; Sharapov, SE; Contributors, J (2009)
A new analytic expression is derived for the resonant drive of high n Alfvenic modes by particles accelerated to high energy by Ion Cyclotron Resonance Heating. This derivation includes finite orbit effects, and the formalism is completely non-perturbative. The high-n limit is used to calculate the complex particle response integrals along the orbits explicitly. This new theory is applied to downward sweeping Alfven Cascade quasimodes completing the theory of these modes, and making testable predictions. These predictions are found to be consistent with experiments carried out on the Joint European Torus [P. H. Rebut and B. E. Keen, Fusion Technol. 11, 13 (1987)].